Analisis Penanganan Kerusakan Jalan Menggunakan Metode Bina Marga dan Pavement Conditional Index (PCI) Pada Ruas Jalan Kabuh - Tapen - Dimas Ubaidillah; Totok Yulianto; Meriana Wahyu Nugroho; Titin Sundari; Rahma Ramadhani (JURAL RISET RUMPUN ILMU TEKNIK, 2023)
The Kabuh – Tapen thruway is included within the category of Course III Collector road type which may be a interfacing street between Kabuh and Tapen streets. In this ponder, the point was to get the esteem of the harm list along the Kabuh - Tapen street. as a work reference and sort of street harm dealing with. Analysts will utilize the PCI and Bina Marga 1990 strategies as a reference. From the examination of the condition of the Kabuh – Tapen street segment on unbending asphalt at STA. 0+000 – 7+340 based on the Asphalt Condition Record (PCI) strategy, a esteem with an normal of 99% is gotten, demonstrating that the asphalt is in exceptionally great condition. On the adaptable asphalt at STA. 7+340 – 9+234, an normal esteem of 40% is gotten, showing that the street asphalt is in a awful condition. The comes about of the Bina Marga strategy on unbending asphalts gotten a priority order esteem of 7 so that the street is included within the schedule support program, whereas on flexible asphalts a need arrange esteem of 3 is gotten, hence it is included within the street enhancement program.